Fostering Citizenship and English Language Competences in Teenagers Through Task-Based Instruction - Yanilis Romero; Adriana Pérez (Universidad Nacional de Colombia, 2021)
This research analyzes how citizenship and communicative competences can be fostered through a task-based approach to language teaching. This paper proposes the design of a unit with social components as the main meaningful task for the teaching of the English language and for fostering citizenship competencies in A2 level learners. An action research method was used; data collection techniques included observations, diaries, interviews, and students' artifacts. Findings report that tasks might foster English language use if those are designed by taking into account students' context and interests. Furthermore, real-life tasks derived from contextual features can enhance civic engagement and promote values, which can be signals of citizenship.